2021
DOI: 10.3390/ani11082227
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii and Salmonella in Hunted Wild Boars from Two Different Regions in Switzerland

Abstract: Toxoplasma gondii and Salmonella are zoonotic foodborne pathogens that may be transmitted to humans through the consumption of raw or undercooked meat, including game. The aim of this study was to determine the seroprevalence of T. gondii and Salmonella antibodies in wild boars in two different regions in Switzerland. During the hunting season of 2020, a total of 126 diaphragm muscle samples of hunted wild boars were collected and the meat juice of these samples was analysed for pathogen-specific IgG antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…The prevalence of Salmonella in the wild boar population has been studied through the analysis of different matrices. Some authors investigated the seroprevalence from blood serum, diaphragm, or muscle samples, achieving different percentages: 1.27% (141/1103) [ 156 ], 3.6% (14/393) [ 157 ], 4.3% (4/94) [ 158 ], 5% (1/20) [ 159 ], 17% (21/126) [ 160 ], 19.3% (52/269) [ 161 ], 38% (69/181) [ 39 ], and 66.5% (255/383) [ 162 ]. Testing of serum samples can reveal the presence of antibodies against Salmonella spp.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of Salmonella in the wild boar population has been studied through the analysis of different matrices. Some authors investigated the seroprevalence from blood serum, diaphragm, or muscle samples, achieving different percentages: 1.27% (141/1103) [ 156 ], 3.6% (14/393) [ 157 ], 4.3% (4/94) [ 158 ], 5% (1/20) [ 159 ], 17% (21/126) [ 160 ], 19.3% (52/269) [ 161 ], 38% (69/181) [ 39 ], and 66.5% (255/383) [ 162 ]. Testing of serum samples can reveal the presence of antibodies against Salmonella spp.…”
Section: Resultsmentioning
confidence: 99%
“…However, because of the smaller number of females evaluated in this study it is not possible to infer data on higher or lower frequency of detection in relation to the sex of the animals. Other studies have however, reported male wild boars with higher detection rates for T. gondii, ranging from 42% (Bassi et al, 2021) to 60% (Machado et al, 2021). This may be explained by the fact that male wild boars have solitary habits, travel longer distances in search of food when compared to females and young ones, thereby increasing the risk of infection (Machado et al, 2021;Rostami et al, 2017), as oocysts of this pathogen survive for long periods in an aquatic environment (Shapiro et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…The prevalence of Toxoplasma infection in wild boar is influenced by factors such as the age and sex of the animals as well as the season and weather conditions [ 29 , 30 ]. Prevalence varies in different European countries: 40% (range 32–59%) in the Czech Republic [ 31 ]; 48% in Poland [ 32 ]; 29% (range 5–45%) in Sweden [ 33 ]; 16.8% in France [ 34 ]; 62% in Slovenia [ 35 ]; 35% in Switzerland [ 36 ]; and 15.5% in Italy [ 37 ]. In Spain, prevalence also varies between different areas: 14.1% in the Valencian Community [ 30 ]; 39% in Doñana National Park [ 29 ]; 19.4% in Andalusia [ 38 ]; 23.88% in the Extremadura Region and 20.8% in the Sierras de Cazorla, Segura, and Las Villas Natural Park [ 39 ]; and 51.16% in Sierra Morena [ 40 ].…”
Section: Introductionmentioning
confidence: 99%